2019
DOI: 10.3892/ol.2019.10611
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of postoperative cognitive dysfunction and influencing factors of dexmedetomidine anesthesia in elderly patients with colorectal cancer

Abstract: Effect of dexmedetomidine-assisted general anesthesia on early postoperative cognitive dysfunctions in elderly patients with colorectal cancer was explored. In total, 140 patients with radical colorectal cancer under general anesthesia from March 2012 to June 2015 were enrolled in the Guizhou Provincial People's Hospital, including 80 patients in the dexmedetomidine group and 60 patients in the saline group. Surgery conditions were recorded, and the incidence of postoperative cognitive dysfunction (POCD) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…The less years of education and knowledge reserve a patient has, the higher the incidence of POCD ( Scott et al, 2017 ). In the process of surgery, a large amount of blood loss led to circulatory fluctuations and insufficient blood supply to the brain, thereby affecting oxygen supply, brain cell metabolism, and postoperative cognitive function ( Zhang et al, 2019 ). Postoperative pain was related to the occurrence of POCD, and while the relevant mechanism is still unclear at present, it may involve the stress reaction of the body due to pain, inciting a state of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The less years of education and knowledge reserve a patient has, the higher the incidence of POCD ( Scott et al, 2017 ). In the process of surgery, a large amount of blood loss led to circulatory fluctuations and insufficient blood supply to the brain, thereby affecting oxygen supply, brain cell metabolism, and postoperative cognitive function ( Zhang et al, 2019 ). Postoperative pain was related to the occurrence of POCD, and while the relevant mechanism is still unclear at present, it may involve the stress reaction of the body due to pain, inciting a state of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, combined spinal-epidural anesthesia was also superior to general anesthesia with intubation in terms of postoperative cognitive function. We speculate that the relatively poor postoperative cognitive function of patients receiving general anesthesia with intubation was associated with the residual systemic analgesics, which might inhibit the central nervous system [16][17][18][19]. In addition to analgesics, pain may also contribute to the development of postoperative cognitive dysfunction [20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…The pathogenesis of postoperative cognitive dysfunction in elderly patients is not clear yet. A study has confirmed that anaesthesia will affect postoperative cognitive function of patients 4 . Therefore, what kind of effective anaesthesia regimen can effectively reduce the postoperative adverse reactions of elderly patients undergoing abdominal surgery has been a hot topic in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…A study has confirmed that anaesthesia will affect postoperative cognitive function of patients. 4 Therefore, what kind of effective anaesthesia regimen can effectively reduce the postoperative adverse reactions of elderly patients undergoing abdominal surgery has been a hot topic in clinical research. In recent years, with the continuous progress of medical technology, the application of total intravenous anaesthesia (TIVA) in surgery has achieved satisfactory results.…”
mentioning
confidence: 99%